Multiple transforming regions of human cytomegalovirus DNA. - el-Beik, T (1986)
The transforming (focus forming) activity of defined cloned DNA fragments from human cytomegalovirus Towne and AD169 was carried out in immortalized rodent cells. The frequency of focus formation in NIH 3T3 cells by Towne XbaI fragment E was 80- to 100-fold higher than that observed with Towne XbaI fragments AO, O, C, or carrier DNA alone but was similar to that observed with pCM4127, a transforming fragment from HCMV AD169 (J. A. Nelson, B. Fleckenstein, D. A. Galloway, and J. K. McDougall, J. Virol. 43:83-91, 1982; J. A. Nelson, B. Fleckenstein, G. Jahn, D. A. Galloway, and J. K. McDougall, J. Virol. 49:109-115, 1984). Foci were first detected in Towne XbaI fragment E-transfected NIH 3T3 cells at 5 to 6 weeks posttransfection, whereas foci were detected at 2 to 3 weeks after transfection with AD169 pCM4127. Digestion of Towne XbaI fragment E with BamHI did not significantly reduce its focus-forming activity. When BamHI subclones of Towne XbaI fragment E were assayed individually for focus formation in NIH 3T3 and Rat-2 cells, transforming activity was localized within each terminal fragment (EJ and EM). Foci induced by EJ or EM DNA alone were smaller compared with those induced by Towne XbaI fragment E. Isolated focal lines exhibited growth in soft agar and were tumorigenic in immunocompetent syngeneic animals. High-molecular-weight DNAs from transformed and tumor-derived lines were analyzed by Southern blot hybridization with intact EM and a 1.5-kilobase subfragment lacking cell-related sequences. Virus-specific EM sequences were detected at less than one copy per cell in Towne XbaI fragment E-transformed NIH 3T3 cells and at multiple copies in rat tumor-derived cell lines. In contrast, virus-specific EJ sequences were barely detected in EJ-transformed and tumor-derived lines with intact EJ as probe.